Peningkatan Pengetahuan Demam Berdarah Santri Melalui Penyuluhan Pencegahan Demam Berdarah Di TPA Ash-Sholeh - Romdani, Irvan; Apriliya, Ayu; Fauzi Anwar Hidayat; Siti; Samsul Hadi (Jurnal Abdikarya Pembangunan, 2024)
Abstract:The emergence of cases of death due to dengue fever has caused anxiety and concern among residents about the high possibility of contracting dengue fever. There is a desire to immediately start real efforts to prevent this, especially in the TPA environment where there are many children who are studying the Koran. Apart from increasing students' knowledge and understanding of dengue fever prevention, this movement aims to maintain the continuity of the teaching and learning process so that it can run smoothly. Children can still learn the Al-Quran and explore the real values of living together with their environment. Service Uses the PAR method so that service members, students and the community actively make changes determined together. Dengue fever prevention outreach activities can increase students' knowledge and understanding of dengue fever material. Increased knowledge of dengue fever by 37.5%, knowledge of the characteristics of the Aedes aegypti mosquito by 48.67% and the time when mosquitoes attack humans by 31.25%. Changes in knowledge and understanding occur due to the involvement of parents in counseling activities and the use of learning multimedia so that information is more easily absorbed. The question and answer process guided by the presenter and the involvement of parents further increased the students' understanding of the material on dengue fever prevention. This encourages students' enthusiasm to use their knowledge to protect themselves and their environment from dengue fever. Furthermore, it is necessary to carry out practical activities to protect oneself and the environment at school and at home so that students can have a real impact in preventing dengue fever. Keywords: Children, Dengue Fever, Extension Program, Santri, Knowledge, Abstrak: Munculnya kasus kematian akibat demam berdarah menimbulkan keresahan dan kekhawatiran warga terhadap tingginya kemungkinan terjangkit demam berdarah. Terdapat keinginan untuk segera memulai upaya nyata pencegahan tersebut, terutama di lingkungan TPA yang banyak terdapat anak-anak yang sedang belajar Al-Qur;an. Selain peningkatan pengetahuan dan pemahaman santr I terhadap pencegahan demam berdarah, gerakan ini bertujuan menjaga keberlangsungan pelaksanaan proses belajar mengajar sehingga dapat berjalan lancar. Anak-anak tetap dapat belajar Al-Qura’n dan mendalami nilai-nili hidup bersama dengan lingkungannya secara nyata. Pengabdian Menggunakan metode PAR supaya pihak pengabdi, santri dan masyarakat aktif melakukan perubahan yang ditetapkan bersama. Kegiatan penyuluhan pencegahan demam berdarah dapat meningkatkan pengetahuan dan pemahaman santri terhadap materi penyakit demam berdarah. Peningkatan pengetahuan demam berdarah sebesar 37.5%, pengetahuan ciri-ciri nyamuk Aedes aegypti 48,67%dan waktu kapan nyamuk menyerang manusia 31.25%. Perubahan pengetahuan dan pemahaman terjadi karena adanya keterlibatan orang tua dalam kegiatan penyuluhan dan penggunaan multimedia pembelajaran sehingga informasi lebih mudah diserap. Proses tanya jawab yang dipandu pemateri dan keterlibatan orang tua semakin menambah pemahaman santri terhadap materi pencegahan demam berdarah. Hal ini mendorong semangat santri untuk menggunakan pengetahuannya dalam menjaga diri dan lingkungannya dari penyakit demam berdarah. Selanjutnya diperlukan kegiatan praktik menjaga diri dan lingkungan yang dilakukan di sekolah dan di rumah sehingga santri mendapatkan dampak nyata dalam pencegahan demam berdarah. Keywords:Anak, Demam Berdarah, Pengetahuan, Penyuluhan, Santri.